Estudo da adsorção e dessorção do corante têxtil Crimson HEXL empregando diferentes carvões ativados - Monarin, Mauricio Marcelo Sinhorim (2012)
The dyes are present in many plants, producing toxic and carcinogenic effluents that significantly affecting the environment when disposed of untreated. The most commonly used methods for dye removing are biological treatment, coagulation / flocculation / membranes and adsorption processes. The present study aims to evaluate the adsorption of reactive dye textile Crimson HEXL, used in industrial plants (mainly laundries) using two commercial activated carbons: the origin of bovine bones (CAO) and bituminous minerals (CAM). To compare the potential application of these two types of carbons, experiments were performed characterization and adsorption in batch system and in duplicate, consisting of the following steps: i) obtaining from the point of zero charge (pHpzc) for each carbon, ii) evaluate the influence the pH of the dye solution, iii) determine the optimal particle size of the adsorbent, iv) to investigate the influence of the stirring rate in the adsorption process, data acquisition and modeling using kinetic models available in the literature, of obtaining data of equilibrium and modeling at different temperatures using literature modeling, v) desorption of the dye in the best conditions for the particular adsorption system carbon-dye (pH and type of eluent). The experiments showed the best conditions of particle size (approximately 20-30 mesh), shaking (100 rpm) and pH of 2. The kinetic data showed a contact time of 48 hours for the system to reach equilibrium. The kinetic model Pseudo-First-Order, Pseudo-Second-Order and intra-particle diffusion showed good fits of the experimental data with high coefficients of determination and high degree of significance for each parameter in the models studied (p-level < 0,05) for the experimental equilibrium data for systems Crimson HEXL CAO and Crimson HEXL CAM, except for the model of intra-particle diffusion at 100 mg/L of system Crimson HEXL CAO. The simulation using the Langmuir model using as adsorbent CAO represented satisfactorily equilibrium data experimental temperatures of 20, 30, 40 and 50 ° C, unlike the Freundlich model which had adjustment only for the temperature of 20 ° C. To the system Crimson HEXL - CAM did not obtain a proper fit for simulating the experimental data using the equilibrium model isotherm Langmuir and Freundlich. The thermodynamic parameters ΔHº, ΔGº and ΔSº were evaluated and demonstrated that the adsorption of the reactive dye Crimson HEXL in CAO and CAM is an endothermic and spontaneous process. The recovery of activated carbons with reactive dyes had poor results for the recovery of the adsorbent for reuse in adsorption processes.